Kosovo : Gender Gaps in Education, Health, and Economic Opportunities - World Bank (World Bank, Washington, DC, 2017)
Kosovo is one of the poorest countries in Europe (World Bank 2010). In 2009, 35 percent of the population lived below the poverty line. This note was prepared primarily as a key input to the Kosovo country partnership strategy (FY2012 to FY2015) and aims to provide an overview of gender disparities in three major domains: human capital, labor market, and entrepreneurship. The note provides a broad picture of gender disparities in Kosovo in education, health, and access to economic opportunities. Lack of statistical data on Kosovo, and particularly of gender-disaggregated data, limits the depth and scope of this gender diagnostic. Men and women in Kosovo have lower education levels than men and women in the European Union (EU). Women comprise less than 10 percent of all entrepreneurs and 0.3 percent of top management positions. This note is organized as follows: section one highlights gender differences in human capital focusing on education and health outcomes; section two describes men's and women's relative employment patterns; section three focuses on gender disparities in entrepreneurship and career advancement in business and politics; and section four provides concluding observations.